Distancia de siembra y dosis de nitrógeno en cultivares de caraota (Agroindustria, Sociedad y Ambiente, 2018)
Nitrogen as an essential element and the sowing distance tend to alter growing and productivity of black bean crops. The study objective was to evaluate growing and productivity of two black bean crops in response to two sowing distances and (N) nitrogen doses. This experiment was conducted in field located at Palaciero's location, Lara state. The experimental design used was aleatory blocks disposed in horizontal fringes for cultivates (Tuiuiú and Uirapurú), vertical rows for sowing distances (0,45 and 0,75 m), and in intersection of both nitrogen doses (0, 20, 60, 100, 140 kg ha-1), with three repetitions. It was applied nitrogen fertilization with Urea at sowing, and 22 days later of sowing (dls) and before flowering. The Uirapuru cultivate overcame (P
Keywords: Performance components; fertilization; Phaseolus vulgaris L